Meningkatkan Hasil Belajar Siswa Kelas X MAN 1 Bombana Pada Materi Dinamika Hidrosfer dan Dampaknya Terhadap Kehidupan dengan Menerapkan Model Pembelajaran Inkuiri Terbimbing - Selny Nafila; La Ode Amaluddin; Surdin Surdin; La Harudu (Jurnal Penelitian Pendidikan Geografi, 2025)
Inappropriate learning models often make the learning process less effective. This study aims to: 1) improve student learning activities; 2) improve teacher teaching activities; and 3) improve student learning outcomes of class X Islamic Senior High School 1 Bombana on the material Hydrosphere Dynamics and Its Impact on Life. The method used in this study is Guided Inquiry. Data collection techniques in this study used written tests, observation, and documentation. The results of the study showed: 1) student learning activities obtained an average score in cycle I of 2.6 and cycle II of 3.2; 2) teacher teaching activities showed an average score of cycle I of 2.8 and cycle II of 3.5; 3) student learning outcomes through tests obtained an average score of cycle I of 70 and cycle II of 81. The Guided Inquiry learning model on the material Hydrosphere Dynamics and Its Impact on Life applied to class X Islamic Senior High School 1 Bombana is quite effective and can improve student learning outcomes.